Political Leadership Through the Lens of Social Media - Bajrami Demush (SEEU Review)
There is currently a global debate about the so-called media transformation, or metamorphosis, which is mainly concerned with technological benefits in the realm of information. This argument focuses on the relationship between "social media" and new media realities, specifically the impact that these platforms have on the development of political leadership in North Macedonia and the Western Balkans in general.